Work-Life Balance as a Predictor of Organizational Commitment: A Cross-Sectional Study at Kedai Kopitiam Budiman - Putriherlina, Annanisa Ilma (Asosiasi Ahli Administrasi Indonesia, 2026)
Work-life balance has become an important factor shaping employee attitudes and organizational outcomes, especially in service-based sectors such as food and beverage businesses. This study examined the relationship between work-life balance and organizational commitment among employees of Kedai Kopitiam Budiman, focusing on whether employees who experience better balance between work and personal life tend to show stronger commitment to their organization. A quantitative cross-sectional design was used, and data were collected through an online questionnaire completed by all 44 employees using a total sampling approach. Both constructs were measured with validated Likert-scale instruments, and analysis included descriptive statistics, normality testing, and the Spearman rank correlation due to the non-normal distribution of one variable. The findings revealed a moderate and positive correlation between work-life balance and organizational commitment. Employees who reported higher perceived balance were more likely to demonstrate stronger loyalty and attachment to the organization. This statistically significant finding suggests that healthy work-life balance practices may contribute to organizational stability. These results highlight the importance of supportive scheduling, equitable workload distribution, and employee-centered policies in strengthening organizational stability. Future research may explore causal mechanisms or examine which specific work-life balance practices have the strongest long-term impact on employee outcomes.